2021
DOI: 10.1017/s2045796021000305
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality and life-years lost in people with bipolar disorder: an 11-year population-based cohort study

Abstract: Aims Bipolar disorder is associated with premature mortality, but evidence is mostly derived from Western countries. There has been no research evaluating shortened lifespan in bipolar disorder using life-years lost (LYLs), which is a recently developed mortality metric taking into account illness onset for life expectancy estimation. The current study aimed to examine the extent of premature mortality in bipolar disorder patients relative to the general population in Hong Kong (HK) in terms of standardis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
1
28
1
2
Order By: Relevance
“…We also found a reduced YPLL of around 5 years across the study periods in patients with bipolar disorder. This seems to be contrary to the findings of most previous individual studies that assessed SMR (primarily on an annual basis) for bipolar disorder and indicated persistent 3,5,7 or even a widening mortality gap 810 in recent decades. However, our analysis comparing life-expectancy/YPLL estimates of three discrete study periods might be limited by the fact that these periods were categorised according to the middle year of cohort data collection per study irrespective of the length of follow-up and only a small number of studies were included in each of the three study periods.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We also found a reduced YPLL of around 5 years across the study periods in patients with bipolar disorder. This seems to be contrary to the findings of most previous individual studies that assessed SMR (primarily on an annual basis) for bipolar disorder and indicated persistent 3,5,7 or even a widening mortality gap 810 in recent decades. However, our analysis comparing life-expectancy/YPLL estimates of three discrete study periods might be limited by the fact that these periods were categorised according to the middle year of cohort data collection per study irrespective of the length of follow-up and only a small number of studies were included in each of the three study periods.…”
Section: Discussioncontrasting
confidence: 99%
“…1,2 People with bipolar disorder exhibit markedly increased risk of premature death, with an approximately two to three times higher mortality rate relative to the general population. [3][4][5] Natural causes, particularly cardiovascular diseases, respiratory diseases and cancers, are a major contributor to excess mortality associated with bipolar disorder. [3][4][5][6] Literature also consistently has found that patients with bipolar disorder have a greatly elevated rate of unnatural deaths, especially suicide, compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between country comparisons of YLL can be informative but the calculation of disease specific YLL can be prone to country specific differences in health care system and resources, and quality of cause of death statistics, as well as to diagnostic procedures and testing as can be seen in between country comparisons of YLL to COVID-19 (16). Without competing risk of suicide persons with psychiatric disease still have a shorter life expectancy (14,17). Similarly, YLL to COVID-19 is mostly attributable to the fragile comorbid old population (18).…”
Section: Discussionmentioning
confidence: 99%